Production of cokes from pastes obtained by raw hydrocarbon electrocracking - A. I. Nikolaev (Тонкие химические технологии, 2014)
Pastes obtained by the electrocracking of raw hydrocarbons can be used as the basis for coke. Comparison of values of physico-chemical characteristics of cokes obtained from their pastes with similar industrial oil coke showed that cokes produced by pastes electrocracking comply with the requirements for coke brands KNG, KZG, KNA, KZO. This allows assuming that cokes obtained by the coking of electrocracking pastes can be used in the aluminum industry, as well as in the manufacture of abrasives and graphite products.